Evaluasi Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) Pada Proyek Konstruksi di Provinsi Gorontalo - Nazlah Kamila Kadir; Arfan Utiarahman; Moh. Yusuf Tuloli (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
Occupational Safety and Health (OSH) is a critical aspect that must not be overlooked, particularly in construction projects, as such projects involve various potential hazards. Therefore, the proper understanding and strict implementation practices are essential to reduce occupational accidents and to create a safe and healthy working environment. This study aims to compare the implementation of Occupational Safety and Health systems across several construction projects in Gorontalo Province and to analyze the application of the Occupational Safety and Health Management System (OSHMS) within these projects. The results indicate that the implementation in the Bulango Ulu Dam Construction Project achieved the highest percentage score of 99.64%, followed by the Amaris Hotel 2 Extension Project with a score of 53.57%, and the National Police Food Security Warehouse Construction Project with a score of 41.07%. Overall, based on respondents’ assessments, the combined implementation across the three projects reached a percentage score of 64.76%, which is categorized as good. These findings suggest that the implementation of Occupational Safety and Health practices in construction projects within Gorontalo Province is generally at a good level.